Fermentation Ability of Bovine Colostrum by Different Probiotic Strains - Ivana Hyrslova; Gabriela Krausova; Tereza Michlova; Antonin Kana; Ladislav Curda (Fermentation, 2020)
Over the past decade, the use of bovine colostrum and its bioactive components as the basis of functional food and dietary supplements for humans has substantially increased. However, for developing new products enriched with probiotics and bovine colostrum, the influence of colostrum composition on the growth promotion of bacteria still needs to be tested. Therefore, we decided to study the influence of bovine colostrum chemical and mineral composition as well as the content of bioactive compounds (immunoglobulins, lactoferrin, lactoperoxidase) on the growth of ten selected strains from genera Lactobacillus, Lacticaseibacillus, Bifidobacterium, and Enterococcus. After 24 h of fermentation, the growth was assessed based on lactic and acetic acids production evaluated using isotachophoresis, bacterial counts determined by the agar plate method, and change of pH. The production of acids and bacterial counts were significantly (P<0.05) different between selected genera. The change of bacterial counts was correlated with pH, but the correlation between growth and bovine colostrum composition was not proven. The highest growth and production of lactic acid was observed after the fermentation of bovine colostrum by the strains Enterococcus faecium CCDM 922A and CCDM 945.